1997
DOI: 10.1099/00221287-143-5-1745
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes, a resident of lipid-rich human skin, produces a 33 kDa extracellular lipase encoded by gehA

Abstract: Five independent clones of the Propionibacterium acnes P-37 lipase gene (gehA) were obtained in ischerichia coli, and the gene was localized to a 2.75 kb Xhol fragment by subcloning. The five clones were shown to contain the same gene by Southern blotting with a DIG-labelled probe to gehA. The nucleotide sequence of gehA was determined, and shown to contain a single ORF of 1017 kb, encoding a protein of 339 amino acids. The predicted molecular mass was 36 kDa. A 33 kDa (PAGE) radiolabelled polypeptide was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…On the contrary, Dupuis and Boyaval [4], and Dupuis et al [5] reported extracellular or cell wall bound lipase and esterase activities for several Propionibacterium strains. Extracellular lipase has been also reported for P. acidipropionici [21], while the existence of extracellular lipases in the case of cutaneous propionic acid bacteria has been clearly confirmed [12,18].…”
Section: Effect Of Metal Ionsmentioning
confidence: 93%
“…On the contrary, Dupuis and Boyaval [4], and Dupuis et al [5] reported extracellular or cell wall bound lipase and esterase activities for several Propionibacterium strains. Extracellular lipase has been also reported for P. acidipropionici [21], while the existence of extracellular lipases in the case of cutaneous propionic acid bacteria has been clearly confirmed [12,18].…”
Section: Effect Of Metal Ionsmentioning
confidence: 93%
“…Before the genome decipherment, knowledge of the capacity of P. acnes to use skin tissue was limited to a secreted extracellular triacylglycerol lipase, GehA, isolated from P. acnes P-37 (294). This enzyme degrades skin lipids, such as sebum, which may be a crucial activity for skin coloni- zation.…”
Section: P Acnes Genome and Biological Lifestylementioning
confidence: 99%
“…The number of genes sequenced from the cutaneous strains of Propionibacterium is even lower, and includes a lipase [28] and a hyaluronate lyase encoding gene (public databases; see Tab. I).…”
Section: Characterisation Of Genes From Propionibacteriamentioning
confidence: 99%
“…sherm. [21] lipase gehA P. acnes [28] Plasmid-encoded replication proteins putative rolling circle replicase rep P. freud. pLME108 [3,4] putative theta replicase repA P. acidi.…”
Section: Characterisation Of Genes From Propionibacteriamentioning
confidence: 99%